Effects of Homeopathic Mother Tinctures on Breath Alcohol Testing. (12th November 2014) - Boatto, Gianpiero; Trignano, Claudia; Burrai, Lucia; Spanu, Andrea; Nieddu, Maria
Abstract: In some countries, it is illegal to drive with any detectable amount of alcohol in blood; in others, the legal limit is 0.5 g/L or lower. Recently, some defendants charged with driving under the influence of alcohol and have claimed that positive breath alcohol test results were due to the ingestion of homeopathic mother tinctures. These preparations are obtained by maceration, digestion, infusion, or decoction of herbal material in hydroalcoholic solvent. A series of tests were conducted to evaluate the alcoholic content of three homeopathic mother tinctures and their ability to produce inaccurate breath alcohol results. Nine of 30 subjects gave positive results (0.11–0.82 g/L) when tests were taken within 1 min after drinking mother tincture. All tests taken at least 15 min after the mother tincture consumption and resulted in alcohol‐free readings. An observation period of 15–20 min prior to breath alcohol testing eliminates the possibility of false‐positive results.